Digital Poster Plagiarism Perspective of Mui Fatwa Number 1 of 2003 Concerning Copyright - Harniz, Innat Adlan Adillah; Sativa, Annisa (Al-Kharaj: Journal of Islamic Economic and Business, 2025)
This research is motivated by the increasing issue of copyright infringement on posters in the digital era, where the ease of creating and distributing digital works opens up opportunities for plagiarism practices.As technology advances, it is becoming easier for people to find and download images or works that should be protected, such as graphic designs posted online on social media. These designs can be copied and shared quickly, any original creation should automatically be protected. These issues should be reason enough to update the law.Furthermore, this study aims to discuss the causes of digital poster plagiarism in Indonesia, legal protection for creators due to digital poster plagiarism, and analyze the binding force of the MUI fatwa regarding digital poster plagiarism, especially in the perspective of MUI Fatwa Number 1 of 2003. This study uses the Normative Juridical Research Method with a Conceptual approach, by examining MUI Fatwa Number 1 of 2003 concerning Copyright and the applicable laws and regulations in Copyright Law Number 28 of 2014. The results of the study indicate that copyright infringement, imitating or copying concepts, visual elements, and plagiarism through social media without permission from the original creator, especially for this digital poster, is haram. This fatwa expressly recognizes copyright as one of the huquq maliyyah (property rights) protected by sharia (Islamic Law). In this case, public awareness of digital poster plagiarism is very important. Legal defense efforts must be in line with strict law enforcement and adequate punishment for copyright violators by authorities based on existing laws and regulations.